Can Parental Body Dissatisfaction Predict That of Children? A Study on Body Dissatisfaction, Body Mass Index, and Desire to Diet in Children Aged 9–11 and Their Families - Solano-Pinto, Natalia; Sevilla-Vera, Yolanda; Fernández-Cézar, Raquel; Garrido, Dunia (Frontiers in Psychology, 2021)
Body image has been associated with self-care and the assumption of either healthy habits or poor diets and eating disorders. As a vital element in the formation of a positive body image, the role of the family in childhood has been highlighted by a few studies. This study aimed to assess whether children's body dissatisfaction could be predicted by their parents’ body dissatisfaction, body mass index (BMI), and approach to change. The sample consisted of 581 participants (366 parents and 215 children). The following instruments were used: anthropometric data, the Brief Scale of Body Dissatisfaction for Children, the IMAGE questionnaire (approach to change and drive for muscularity subscales), and the Eating Disorder Inventory-2 (body dissatisfaction and drive for thinness subscales). The results indicated that 19% of children, 22.8% of mothers, and 70.2% of fathers were overweight or obese. The multiple regression models developed for boys and girls explained 60% and 57% of the variance in body dissatisfaction, respectively. Several variables attributable to the mother (higher approach to change, higher drive for thinness, and higher BMI) and to the boys themselves (drive for muscularity, approach to change, and having a high BMI percentile) predicted a higher level of body dissatisfaction. For girls, only variables regarding themselves (approach to change, age, and BMI percentile) explained their body dissatisfaction. Relationships with the traits of the father were not detected for both models. The influence of sociocultural factors on the construction of gender and the negative consequences of mothers’ dieting for aesthetic purposes, on the development of children's body image, are discussed.